The Effect of Process Based Approach on Seventh Grade Students’ Writing Achievement - Blangsinga, Aditya; Padmadewi, Ni Nyoman; Juniarta, Putu Adi Krisna (Universitas Pendidikan Ganesha, 2019)
This study aimed at investigating the implementation of the process based approach in teaching writing in order to know its effect to the improvement of students’ writing achievement Furthermore, the quantitative method was used in this research with quasi experimental design. The subjects involved in this study were 35 Junior High School students from VII A7 class in SMP Negeri 1 Singaraja, Bali, Indonesia. The proficiency test such as pretest and post test were conducted in this study in oder to collect the data. The students were given a treatment for about eight weeks. The data obtained were analysed by using descriptive and inferential statistics. It was analyzed using SPSS. As the result of statistical analysis, it was found that sig 2-tailed result in the paired samples t-test wast 0.00, which was below 0.05. In terms of the mean score, it was found the mean score in the post test (80.46) was higher than the mean score in the pretest (68.59). So, it can be concluded that process based approach had a significant effect on the seventh’ grade students writing achievement.